Tailoring the structure of polysulfone nanocomposite membranes by incorporating iron oxide doped aluminium oxide for excellent separation performance and antifouling property. Issue 5 (31st March 2022) - Sherugar, Prajwal; Déon, S.; Nagaraja, K. K.; Padaki, Mahesh
Abstract : Simple yet powerful strategy is developed for the fabrication of iron oxide doped aluminium oxide composite nanoparticles and investigated its role in membranes as novel nanoadditives for achieving excellent productivity and selectivity upto 120 h. Abstract : This present investigation reports an effective method for the fabrication of iron oxide doped aluminium oxide (Fe:Al2 O3 ) composite nanoparticles and the potential of the nanocomposite membranes as novel nanoadditives for enhancing productivity and selectivity. The nanoparticles were prepared by the solution combustion method using aluminium nitrate nonahydrate and ferrous nitrate as the aluminium and iron precursor, respectively. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analysis revealed that both aluminium and iron is in +3 oxidation state. From the FESEM cross-sectional image, the porous nature and finger-like voids of the membranes were observed and it revealed that the addition of Fe:Al2 O3 nanoparticles enhances the porosity of the membranes. The separation performances of the developed membranes were analyzed by using different feed solutions under different operating conditions and this highlighted that the nanocomposite membrane incorporated with 1.25 wt% nanoparticles exhibits excellent productivity (130 LMH) and selectivity performance. The optimized mixed matrix membrane displayed rejection efficiencies of 99 ± 0.6%, 98 ± 1%, 62 ± 2% and 48 ± 1% for Pb 2+, Cd 2+, Hg 2+ and F −, respectively at 2 bar operating pressure. Further, the antifouling behavior of the membranes was investigated using mixed foulants (BSA, Pb 2+, Cd 2+ ) as the feed solution and the optimized membrane showed excellent antifouling ability. Afterwards, a long-term study was conducted up to 120 hours using wastewater containing mixed foulants as the feed solution and a rejection greater than 90% was achieved with stable flux. The developed membranes were well-balanced in both productivity and selectivity even after repeating several cycles, which reveals their capability for an effective treatment of wastewater containing toxic heavy metal ions.